Pemanfaatan Citra Satelit Google Earth untuk Penilaian Progres Pemulihan Lahan Pasca 15 Tahun Tsunami Aceh di Kecamatan Lhoong, Aceh Besar - Ismiatul Ramadhian Nur; Syamsidik Syamsidik; Saumi Syahreza (Jurnal Rekayasa Elektrika, 2021)
The 2004 Indian Ocean Tsunami has changed the land cover of the affected areas. Sixteenth years after the tsunami, studies pertinent to land restoration progress are becoming crucial as one of the needs in assessing the progress of the long-term disaster recovery process. Spatio-temporal land change assessment in a disaster-affected area can be conducted using time-series satellite imagery. One of them is The Google Earth satellite image which has an adequate prior data record. Although it has a single band, the Google Earth satellite imagery has many other advantages: easy access, free of charge, and decent resolution for detailed mapping. This research aims to assess the progress of land restoration by utilizing Google Earth satellite imagery. The applied method is visual observation and on-screen digitization process by Google Earth Pro and QGIS. This study provides outcomes of the trend of land transformation after the tsunami, which shows that the rice fields and ponds have not recovered to the condition before the tsunami. Meanwhile, the length of the road and building area have exceeded the pre-tsunami time. The entire land uses show an increasing trend with varying percentages from 2010 to 2020. This research is essential to carry out as an initial assessment of the long-term recovery process, especially related to the livelihood conditions of survivors after the 15 years of the tsunami, which is monitored through land cover.